Werner Richard Heymann in Hollywood: a case study of German-Jewish emigration after 1933 as a transnational experience. Issue 1 (3rd May 2016) - Schlör, Joachim
Abstract: This contribution presents aspects of the life and work of the pianist and composer Werner Richard Heymann (1896–1961) and asks what the experience of that exile in Los Angeles – frightening and exhilarating at the same time – meant for him. In order to better understand his role in the transatlantic exchange of musical and literary ideas and practices, his particular story will be placed in the wider framework of transnationalism as a specific experience in the context of German-Jewish emigration after 1933. In order to get a clearer picture of the conditions in Los Angeles and Hollywood, the paper also looks at documents concerning the situation in New York where Heymann's friend and colleague Robert Gilbert (1899–1978) spent the War years.